139k views
3 votes
Como resolver a equação -7. (x-3)=x +5

User Ralpharoo
by
6.7k points

1 Answer

4 votes

Answer:


x=2

Explanation:


-7(x-3)=x+5

Distribute the
-7 into
(x-3):


-7x+21=x+5

Subtract
x from both sides of the equation:


-8x+21=5

Subtract
21 from both sides of the equation:


-8x=-16

Divide both sides of the equation by the coefficient of
x, which is
-8:


x=2

_

Check your work by substituting
2 into the initial equation:


-7(2-3)=2+5


-14+21=2+5


7=7

The answer is correct!

User Hetaoblog
by
5.1k points